Theoretical Investigation of the Controlled Metathesis Reactions of Methylruthenium(II) Complexes with Terminal Acetylenes. Issue 15 (22nd April 2014) - Liu, Yuxia; Chen, Guang; Wang, Hongliang; Bi, Siwei; Zhang, Dongju
Abstract: With the help of density functional theory (DFT) calculations, we theoretically investigated and rationalized the controlled metathesis reactions of methylruthenium complex trans ‐[Ru(CH3 )2 (dmpe)2 ] [dmpe = 1, 2‐bis(dimethylphosphanyl)ethane] (A ) with terminal acetylenes. On the basis of the mechanistic study, two important issues related to the generation of mono‐ and bis‐acetylido Ru complexes have been addressed. One issue is why the formation of bis‐acetylido complexC, trans ‐[Ru(C≡CPh)2 ] (dmpe)2, is more difficult than the formation of mono‐acetylido complexB, trans ‐[Ru(C≡CPh)(CH3 )(dmpe)2 ]. A strong d→π*(C≡C) interaction between Ru and the alkynyl inB is believed to weaken π back‐donation of Ru to the phenylacetylene C–H σ* bond, and then makes the phenylacetylene C–H bond difficult to break. The second issue is what role methanol plays in promoting the ligand metathesis between the methyl group inB and one alkynyl moiety in 1, 4‐diethynylbenzene to give bis‐acetylido speciesD, trans ‐[(PhC≡C)Ru(dmpe)2 (C≡CC6 H4 C≡CH)]. The relatively strong proton‐donating ability of methanol was found to be the major reason. The present study is indicative of the controllable synthesis of mono‐ and bis‐acetylido, and even di‐ and trinuclear acetylide‐bridged ruthenium(II) complexes. Abstract : DFT calculations have been performed to study the controlled metathesis mechanisms of trans ‐[Ru(CH3 )2 (dmpe)2 ] [dmpe = 1, 2‐bis(dimethylphosphanyl)ethane] with terminal acetylenes. Two important issues have been addressed, one of which is the role methanol plays in promoting the ligand metathesis between the methyl group and one alkynyl moiety.